Using English from conversation to canon (London [England] : Routledge in association with the Open University, 1996)
Everyday talk. Literacy practices in English. English at work. Rhetoric in English. What makes English into art? Language play in English. An English canon?...
Keywords: English language; English language -- Social aspects -- English speaking countries -- Problems, exercises, etc; English language -- Spoken English -- English-speaking countries -- Problems, exercises, etc; Intercultural communication -- Problems, exercises, etc; English philology